Analisis Pengontrolan Water Treatment Bandara Djalaluddin Menggunakan Sistem Kerja Star Delta - Sianaga, Anastasya H.B.K; Hidayat, Jhoni; Fitriani, Ayu (MASALIQ, 2024)
In knowing how efficient the use of the Star Delta circuit is, the need for a circuit on a 3 Phase motor and how to apply the circuit to a 3 Phase water pump motor. The research was conducted at Gorontalo Djalaluddin Airport which is located in Isimu Sel, Tolotio, Tibawa District, Gorontalo Regency, Gorontalo, Indonesia. The research was carried out using data collection methods. An example of the application of a star delta circuit to a water pump motor. An electric motor is included in the category of dynamic electric machines and is an electromagnetic device that converts electrical energy into mechanical energy. Electric motors in the industrial world are often referred to as the industrial "work horse" because it is estimated that in an industry the average electricity consumption for electric motors is around 65-70% of the total electrical load in the industry. Three-phase electric motors have initial current characteristics that are 5 to 7 times the nominal current of the electric motor itself, but can be overcome by a star (Y) - triangle (Δ) starting system. The aim of this study was to examine how the triangular (Δ) star (Y) starting system works for 3 phase induction motors. The methods used include literature studies, collection of tools and materials, design, tool testing and data collection. From the results of testing the triangular (Y) star starting system (Δ) effectively suppresses the high starting current of the electric motor operation with the value of the measurement results of electric current using a star connection (Y) in the R phase of 0.6 A, the S phase of 0.8 A and the T phase of 0.6 A. And using a triangular relationship (Δ) in the R phase of 7.5 A, the S phase of 8.5 A and the T phase of 8.3 A.